Biochar promotes compost humification by regulating bacterial and fungal communities - Zhang, Junying; Fan, Bowen; Zhao, Liqin; Zhao, Changjiang; Yang, Fengjun (Frontiers in Microbiology, 2024)
Humus can be formed during composting through biological pathways, nonetheless, the mechanisms through which bacterial and fungal communities govern the development of humus in compost with the addition of biochar remain uncertain. In this study, compost with cow dung and maize stover as feedstock was employed as a control group, and compost with 10% biochar added on top of the feedstock was adopted as a treatment group to investigate the effect of bacterial and fungal communities on humus formation during biochar composting. The results demonstrated that the humic acid content increased by 24.82% and 25.10% at the cooling and maturation stages, respectively, after adding biochar. Besides, the degree of polymerization content in the maturation stage was elevated by 90.98%, which accelerated the humification process of the compost. During the thermophilic and maturity stages, there was a respective increase of 51.34% and 31.40% in reducing sugar content, suggesting that the inclusion of biochar could furnish ample reducing sugar substrate for the Maillard reaction. The addition of biochar reduced the number of humus precursor-associated genera by 35, increased the number of genera involved in humus synthesis by two, and enhanced the stability of the cross-domain network between bacteria and fungi, which confirms that microorganisms contribute to the humification process by decreasing humus precursor consumption as well as increasing humus synthesis with the addition of biochar. Additionally, adding biochar could enhance the humification capacity of the compost pile by dominating the Maillard reaction with reducing sugars as the substrate and strengthening the function of humus synthesis-associated genera. This study enhances our comprehension of the regulatory pathways of biochar in the humification process during composting.